2014
DOI: 10.1021/es502437e
|View full text |Cite
|
Sign up to set email alerts
|

First Day of an Oil Spill on the Open Sea: Early Mass Transfers of Hydrocarbons to Air and Water

Abstract: During the first hours after release of petroleum at sea, crude oil hydrocarbons partition rapidly into air and water. However, limited information is available about very early evaporation and dissolution processes. We report on the composition of the oil slick during the first day after a permitted, unrestrained 4.3 m(3) oil release conducted on the North Sea. Rapid mass transfers of volatile and soluble hydrocarbons were observed, with >50% of ≤C17 hydrocarbons disappearing within 25 h from this oil slick o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 105 publications
(262 reference statements)
4
57
0
Order By: Relevance
“…Numerous reports have appeared since the 1970s on the role of evaporation after an oil spill (Mackay and Shiu, 1976;Fingas, 1995;Gros et al, 2014a). In modeling crude oil evaporation rates and mechanisms, Fingas (1995) found that up to 75% of light crude oil volume evaporates after the first few days following an oil spill.…”
Section: Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have appeared since the 1970s on the role of evaporation after an oil spill (Mackay and Shiu, 1976;Fingas, 1995;Gros et al, 2014a). In modeling crude oil evaporation rates and mechanisms, Fingas (1995) found that up to 75% of light crude oil volume evaporates after the first few days following an oil spill.…”
Section: Evaporationmentioning
confidence: 99%
“…In modeling crude oil evaporation rates and mechanisms, Fingas (1995) found that up to 75% of light crude oil volume evaporates after the first few days following an oil spill. A mass transfer model developed by Gros et al (2014a) to describe the first day of an oil spill showed evaporation to be the dominant fractionation process. Aerosol formation by wind and wave action can also transfer oil components into the atmosphere (Arey et al, 2007;Aeppli et al, 2013).…”
Section: Evaporationmentioning
confidence: 99%
“…The enhanced technical standards for oil production has reduced large spills (which ranges from 7-700 tons and above 700 tons of oil) drastically during the past decades to an average of 5.2% for the 7-700 tons and 1.8% for those above 700 tons per year, whiles smaller spills (less than 7 tons of oil) representing an estimated 80% of all recorded spill has been going unnoticed and unreported [3]. The concentration of dissolved and dispersed hydrocarbons that marine organisms are exposed to is highest during initial stages of the spill [5,6]. Hence the major toxicity mechanisms for smaller spills are from immediate exposure which disappears from sight during the first few days without the oil been necessarily degraded from the sea surface [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also rising demands for marine oil exploration is likely to increase rather than decrease hence an increased frequency of small spills. Various researches has documented oil toxicity at its highest during the initial stages of a spill [5,6] hence even smaller spills can possibly cause prolonged impacts and pose a serious risk to marine ecosystem health and biota. For instance, major shipping routes on the North Sea is recurrently contaminated with oil, either from unintentional spills or maybe from natural oil and gas seeps [5,8] discovered a lot of unsupervised and undocumented spills within the major shipping routes on the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, to what extent do evaporation and sedimentation reduce the inputs to the shortterm hydrocarbon cycle? For a recent controlled release experiment in the North Sea, 95% of n-pentadecane was found to evaporate within the first day following a surface release (18). Finally, the concentration of oil during an active spill is likely to exceed the concentration of cyanobacterial hydrocarbons by a factor of a million, with dramatic implications for access to substrate and nutrients by the microbial responders.…”
mentioning
confidence: 99%